Participant Characteristics in Human-in-the-Loop Studies with Multiple Unmanned Vehicles including Aircraft. (September 2022) - Bass, Ellen J.; Amey, Rachel; Glavan, Joseph; Read, Tyler; Raghunath, Nisha; Sanchez, Christopher; Silas, Katie; Haritos, Tom; Adams, Julie A.
The characteristics that a supervisor of multiple autonomous and semi-autonomous systems should possess remain unclear. Determination of these qualities would support job performance as well as recruiting and training. To evaluate the human characteristics currently being considered by human-in-the-loop experiments, a review of the multiple remote vehicle supervision literature was conducted. The human characteristics addressed included: gender, domain relevant experience, working memory, supervisory relevant skills and abilities (e.g., visual skills, spatial ability, attentional control, vigilance), and traits related to multi-tasking (e.g., stress, resilience). The discussion identifies gaps in the current state of the art with respect to the consideration of human characteristics for multi-autonomous and semi-autonomous systems supervision where at least one vehicle is an aircraft.